PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI (Studi pada Pegawai Negeri Sipil di Dinas Sosial Kabupaten Kendal) - Fidayah Yuli Ernawati; Siti Rochmah (JURNAL STIE SEMARANG, 2019)
The purpose of this study was to find out the Motivation and Work Discipline partially or simultaneously on Employee Performance (studies on Civil Servants at the Kendal District Social Service). The method used in this research is Multiple Regression Analysis. This research was conducted on Civil Servants in the Kendal Social Service Office of Kendal. The results showed that Motivation had a significant positive effect on Employee Performance (studies on Civil Servants in the Kendal District Social Service), Work Discipline had a significant positive effect on Employee Performance (Study on Civil Servants in the Kendal District Social Service).